2021
DOI: 10.1080/13696998.2021.1887877
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the economic value of Ceribell Rapid Response EEG in the inpatient hospital setting

Abstract: Aims: Potentially life-threatening diagnosis of non-convulsive status epilepticus (NCSE) can only be confirmed with electroencephalography (EEG). When access to EEG is limited, physicians may empirically treat, risking unnecessary sedation and intubation, or not treat, increasing risk of refractory seizures. Either may prolong hospital length of stay (LOS). The current study aimed to examine the effect of a new EEG system (Ceribell Rapid Response EEG, Rapid-EEG) on hospital costs by enabling easy access to EEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…We found relatively high rates of antiseizure medication treatment preceding pocEEG monitoring, however we did not observe any significant differences in pre‐pocEEG anti‐seizure medication treatment rates associated with subsequent pocEEG detection of epileptiform versus non‐epileptiform activity, suggesting that clinical suspicion alone can be unreliable in diagnosing such abnormalities. This same phenomenon was previously demonstrated in the Does Use of Rapid Response EEG Impact Clinical Decision Making (DECIDE) multicenter study of Ceribell pocEEG, and a subsequent economic analysis projected the financial impacts of inappropriate or inaccurate treatment in terms of excess rates of intubation and prolonged ICU and hospital length of stay ranged from $3971 to $17,290 per patient 4,14 …”
Section: Discussionsupporting
confidence: 62%
“…We found relatively high rates of antiseizure medication treatment preceding pocEEG monitoring, however we did not observe any significant differences in pre‐pocEEG anti‐seizure medication treatment rates associated with subsequent pocEEG detection of epileptiform versus non‐epileptiform activity, suggesting that clinical suspicion alone can be unreliable in diagnosing such abnormalities. This same phenomenon was previously demonstrated in the Does Use of Rapid Response EEG Impact Clinical Decision Making (DECIDE) multicenter study of Ceribell pocEEG, and a subsequent economic analysis projected the financial impacts of inappropriate or inaccurate treatment in terms of excess rates of intubation and prolonged ICU and hospital length of stay ranged from $3971 to $17,290 per patient 4,14 …”
Section: Discussionsupporting
confidence: 62%
“…Noninvasive mobile EEG solutions could also have an impact on the economy of health services 71 . The possibility to automatically detect seizures could decrease the time spent by clinicians reviewing EEG for conventional assessment and can be useful in patients with a low frequency of events 72,73 .…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive mobile EEG solutions could also have an impact on the economy of health services. 71 The possibility to automatically detect seizures could decrease the time spent by clinicians reviewing EEG for conventional assessment and can be useful in patients with a low frequency of events. 72,73 The cost of the systems may be lower compared to conventional in-hospital scalp EEG and may not be limited by the availability of hospital resources.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies suggest the implementation of RRLM-EEG may reduce overall healthcare costs. Ney et al evaluated RRLM-EEG cost-benefits in the hospital and found that each use of RRLM-EEG as a Rapid-EEG system saved between $3971 and $17,290 [ 25 •]. These cost-benefits result from reduced hospitalizations and unnecessary use of antiseizure medications in those with suspected NCSE [ 26 28 ].…”
Section: Cost and Accessibilitymentioning
confidence: 99%